Hands-On Full-Stack Development with Swift : Develop full-stack web and native mobile applications using Swift and Vapor. - Patel, Ankur (Packt Publishing, 2018)
Swift, with server-side coding, has become the future of native app development not only on iOS but for watchOS and tvOS. This book will show you how to create a native shopping list app along with a Full-Stack backend using Vapor. Vapor will serve as an API server for the mobile app and also as a web server to serve dynamic web pages to the ...